Knowledge preservation and curation - Foster, Margie; Arvind, Hossein; Graham, Hugh T.; Bedford, Denise (Emerald Publishing Limited, 2023)
In order to achieve its full value, knowledge must flow and be continuously used. Knowledge use, reuse, and repurposing has been a challenge discussed in knowledge sciences literature for over three decades. Based on a review of research and conversations with business stakeholders, the authors investigate and offer solutions to two key challenges - preserving and curating knowledge. Knowledge Preservation and Curation focusses on business value and processes rather than traditional legal and financial requirements, and further, explores preservation and curation in known and unknown business futures. Real-world examples from cutting-edge private and public sector organizations are included, and give unique insight into the world of knowledge management.
Includes index.
Keywords: Knowledge management.; Business & Economics -- Information Management.; elektronické knihy; electronic books